A Dialogue on the Banks of the Ganges: Gordon Craig and Ananda Coomaraswamy - Ribeiro (University of São Paulo, São Paulo/SP, Brazil), Almir (Revista Brasileira de Estudos da Presença, 2022)
This paper analyzes the dialogue between Edward Gordon Craig and Ananda Coomaraswamy, a historian of Indian art, as the launching point of the investigative universe known as intercultural theatre, and the consequences of this dialogue in the thought of the British director, challenging his creation of the Über-marionette. From this dialogue, the text presents Gordon Craig’s cautious stance on trade between cultural traditions. Those inherent idiosyncrasies in these exchanges, which populated the research throughout the 20th and early 21st centuries, are problematized in this article. The debate’s cyclical aspect is exemplified, recovering the clash between Rustom Bharucha, severe critic of Western attempts to Interculturalism, and Richard Schechner, one of the mentors of intercultural theatre.